(untitled) (Revista Iberoamericana de Bioética, 2020)
Inequality between countries demonstrates the fragile nature of the defence of human rights. This text seeks to reflect on access to health in countries of the Global South, specifically a brief analysis of Brazil and Mozambique. It explores the most vulnerable populations in these two countries, based on the statement on protecting peoples’ rights in the Universal Declaration on Bioethics and Human Rights, and also as a reference to the Sustainable Development Goals. Both countries must produce standards that promote equity in health, considering that ethical and urgent actions must be taken to spare human lives.